Menin regulates the serine biosynthetic pathway in Ewing sarcoma. Issue 3 (28th May 2018) - Svoboda, Laurie K; Teh, Selina Shiqing K; Sud, Sudha; Kerk, Samuel; Zebolsky, Aaron; Treichel, Sydney; Thomas, Dafydd; Halbrook, Christopher J; Lee, Ho‐Joon; Kremer, Daniel; Zhang, Li; Klossowski, Szymon; et al.
Abstract: Developmental transcription programs are epigenetically regulated by multi‐protein complexes, including the menin‐ and MLL‐containing trithorax (TrxG) complexes, which promote gene transcription by depositing the H3K4me3 activating mark at target gene promoters. We recently reported that in Ewing sarcoma, MLL1 (lysine methyltransferase 2A, KMT2A) and menin are overexpressed and function as oncogenes. Small molecule inhibition of the menin–MLL interaction leads to loss of menin and MLL1 protein expression, and to inhibition of growth and tumorigenicity. Here, we have investigated the mechanistic basis of menin–MLL‐mediated oncogenic activity in Ewing sarcoma. Bromouridine sequencing (Bru‐seq) was performed to identify changes in nascent gene transcription in Ewing sarcoma cells, following exposure to the menin–MLL interaction inhibitor MI‐503. Menin–MLL inhibition resulted in early and widespread reprogramming of metabolic processes. In particular, the serine biosynthetic pathway (SSP) was the pathway most significantly affected by MI‐503 treatment. Baseline expression of SSP genes and proteins (PHGDH, PSAT1, and PSPH), and metabolic flux through the SSP were confirmed to be high in Ewing sarcoma. In addition, inhibition of PHGDH resulted in reduced cell proliferation, viability, and tumor growth in vivo, revealing a key dependency of Ewing sarcoma on the SSP. Loss of function studies validated a mechanistic link between menin and the SSP. Specifically, inhibition of menin resulted in diminished expression of SSP genes, reduced H3K4me3 enrichment at the PHGDH promoter, and complete abrogation of de novo serine and glycine biosynthesis, as demonstrated by metabolic tracing studies with 13 C‐labeled glucose. These data demonstrate that the SSP is highly active in Ewing sarcoma and that its oncogenic activation is maintained, at least in part, by menin‐dependent epigenetic mechanisms involving trithorax complexes. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.